Where two hearts meet [large type] - Johnson, Liz, 1981- (Johnson, Liz, 1981- Prince Edward Island dreams, 2016)
In her kitchen at the Red Door Inn, executive chef Caden Holt is calm, collected, and competent. But when her boss asks her to show off their beautiful island to impress a visiting travel writer and save the inn, Caden is forced to face a world much bigger than her kitchen -- and a man who makes her wish she was beautiful. Journalist Adam Jacobs is on a forced sabbatical on Prince Edward Island. He's also on assignment to uncover a story. Instead he's falling in love with the island's red shores and Caden's sweets. When Caden discovers Adam isn't who she thought he was, she realizes that the article he's writing could do more than ruin the inn's chances for survival -- it might also break her heart.